The use of quantitative pupillometry in brain death determination: preliminary findings - Lenga, Pavlina; Kühlwein, Daniel; Schönenberger, Silvia; Neumann, Jan-Oliver; Unterberg, Andreas; Beynon, Christopher (Neurological sciences, 2024)
Quantitative pupillometry (QP) has been increasingly applied in neurocritical care as an easy-to-use and reliable technique for evaluating the pupillary light reflex (PLR). Here, we report our preliminary findings on using QP for clinical brain death (BD) determination.